Slim curtain wall spandrel integrated with vacuum insulation panel: A state-of-the-art review and future opportunities. (October 2021) - Boafo, Fred Edmond; Kim, Jin-Hee; Ahn, Jong-Gwon; Kim, Sang-Myung; Kim, Jun-Tae
Abstract: Curtain wall façades have been embraced worldwide as a key sign of modern architecture. To improve the thermal characteristics and energy performance of curtain wall systems (CWS), insulated spandrels are installed between glazing sections. However, there are some noteworthy space-technical constraints. Firstly, CWS are structurally supported by frame systems. The inner length (interior projection) of a curtain wall frame is related to its structural requirements. When high structural performance is not needed, inner length is usually shortened. However, the inner length also creates space for insulation. Due to this space problem, even when high structural performance is not required, the inner length is still enlarged to accommodate the required thickness of insulation. Also, spandrel sections with thick insulated back panels are conventionally installed behind monolithic glazing or opaque claddings between slab/plenum areas of adjacent floors and hidden from the view of building users. Otherwise, aesthetics is compromised due to protrusions. Thus, total area to install insulation in curtain wall façades is traditionally defined and limited to slab/plenum areas only. Consequently, there could be undesirable increase or decrease of window-to-wall ratio as well as restriction of design freedom. Such slim façades require thin and high-performance insulation solutions. Among super-insulating materials currently available, vacuum insulation panel (VIP) is a good go-to insulator to be integrated into curtain wall spandrels. This study seeks to present a comprehensive review on CWS integrated with VIP as spandrel insulation. Depending on the level of prefabrication and how they are built, CWS can broadly be categorized into stick, unitized, and structural glazing systems. Curtain walls differ significantly from conventional windows in that curtain walls are anchored from floor slabs of a building (hangs like a curtain) whereas windows are mounted between floor slabs. Throughout literature, VIP integrated into CWS is composed of fumed silica core material and encapsulated in a metalized laminate (Si-VIP). Under severe accelerated aging conditions, studies proved that VIP spandrel modules provided ten times protection to the VIPs as compared to standalone VIPs. The concept represents a strategy to extend the service life and in-service durability of VIPs, while improving the energy consumption footprint of CWS. As far as the authors know, this paper is the first state-of-the-art review covering CWS integrated with VIP spandrels. Finally, current challenges and future research opportunities concerning VIP integration in CWS are explored. Highlights: Review of curtain wall system (CWS) integrated with vacuum insulation panel (VIP) was conducted. Space-technical constraints of slim curtain walls require thin and high-performance insulation solutions. VIP is a viable insulation for curtain wall spandrel due to its high thermal resistance per unit thickness. Limitations of existing studies on CWS integrated with VIP were presented. Current challenges and future perspectives were discussed.